An Analysis of the Teachings of Muhammad (SAW) to Conceptualize National Professional Standards for Teachers - Muhammad Qasim Ali; Muhammad Asghar Javed al-Azhari; Dr. Muhammad Imran (Journal of Islamic Thought and Civilization, 2020)
Presently, the nations are focusing on skilled manpower. For this purpose, nations are developing professional standards through education for better education. Teachers of a nation called social engineers. Muhammad's (SAW) life is a guiding light for all of humanity. In modern times, quality education and skilled manpower is the solution for social dilemmas. The major objective of the study is to analyze the teachings of Muhammad (SAW) in order to conceptualize national professional standards for teachers. It is concluded from the study that Prophet Muhammad (SAW) took practical life like examples and taught his followers/students through such example whereas the contemporary teachers are in a hurry to finish the syllabus and cover the mentioned curriculum. Basically, the contemporary teachers are not concentrating on the lifelong training of their learners/students. The Holy Prophet Muhammad (SAW) used multiple instructional techniques during his teachings to his followers. The life of Muhammad (SAW) personified that he (SAW) create a teaching-learning environment for the better learning of their followers. It is also perceived from the life of Muhammad (SAW) that he (SAW) stressed the learning of foreign language.